A New Design of Printed Monopole Antenna with Multi-Resonance Characteristics for DCS/WLAN/WiMAX Applications - Ojaroudi, Nasser; Ojaroudi, Mohammad; Ghadimi, Noradin (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a new printed monopole antenna is presented for simultaneously satisfying DCS, wireless local area network (WLAN) and worldwide interoperability for microwave access (WiMAX) applications. The operating frequencies of the proposed antenna are 1.8 GHz, which covers DCS operations, 2.4/5.2/5.8 GHz for WLAN system and 2.5/3.5/5.5 GHz for WiMAX system. The desired first and second resonant frequencies are obtained by adjusting the length of the L-shaped slits. Also by cutting an inverted ?- shaped slot in the radiating patch; multi band performance can be produced. Prototypes of the proposed antenna have been constructed and studied experimentally. The measured results show good agreement with the numerical prediction and good multiband operation.